Backward evaluation in peer assessment: A scoping review. (December 2021) - Misiejuk, Kamila; Wasson, Barbara
Abstract: Implementing backward evaluation as part of the peer assessment process enables students to react to the feedback they receive on their work within one peer assessment activity cycle. The emergence of online peer assessment platforms has brought new opportunities to study the peer assessment process, including backward evaluation, through the digital data that the use of these systems generates. This scoping review provides an overview of peer assessment studies that use backward evaluation data in their analyses, identifies different types of backward evaluation and describes how backward evaluation data have been used to increase understanding of peer assessment processes. The review contributes to a mapping of backward evaluation terminology and shows the potential of backward evaluation data to give new insights on students' perceptions of what is useful feedback, their reactions to the feedback received and its consequences for feedback implementation. Highlights: Backward evaluation can help detect the tit-for-tat strategy. Backward evaluation is mostly used to examine mediators of student feedback uptake. Feedback helpfulness is the most popular metric for backward evaluation.